PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 9 PEKANBARU - Fitryani Handiawati; Syahrilfuddin '; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is motivated by the low value of math. Preliminary data result of learning students of class III of SD Negeri 9 Pekanbaru is from the 35 students, only 20 peoples or 57,14% completed or reached the KKM and 15 peoples or 42,86% were not completed. Based on these problems, it is necessary given way to solve the problem include applying Cooperative Learning Type Make a Matchmodel, helping students to think positively and creatively in every activity, has confidence in his ability, facilitate students social interaction with fellow friends, as well as improving student learning outcomes. Subjects in this research were students of class III of 9 elementary school Pekanbaru. This research was conducted in two cycles, by doing the daily test of the end of each cycle. The result of this research shows that the cooperative type make a match model can increase math studies, completeness math learning outcomes in first cycle is 65,71%, in second cycle increased to 91,42%.Keywords : Cooperative Learning Type Make a Match,Mathematics Learning Outcomes..